PERUBAHAN BUTIR DAN PENENTUAN TEMPERATUR PEMBENTUKAN BARIUM HEXAFERRITE TERSUBSTITUSI ION Mn+2 Dan Ti+4 MELALUI MEKANISME MEKANIKA MILLING - Priyono, Priyono; Manaf, A (BERKALA FISIKA, 2012)
Abstract Ferrite as magnetic material has been exploited for various the application for exampleas electronic peripherals and optic like hard magnetic also soft magnetic materials. For theapplication of high frequency usually exploited as circulator, phase shifter and absorber and antidetection material. In research has been done synthesis and characterization of sewer structuresnanocristall barium phase hexaferrite substitution is partial with ion Manganese and Titaniumthrough mechanics engineering alloy. Indicated that monophase formation of Barium Hexaferriteis substitution by Mn+2 and Ti+4 happened at growth temperature above 7500 C. At low relativetemperature 5000 C and 750 0 C , 8500 C and 10000 C result of plant from mechanics processalloy is not happened formation of phase, but only experiences recrystallization to returnfollowed with magnification growth of grain its. Above heating 7500 C plant grain desisted andhappened orthogonal transformation of off the cuff phase towards formation of bariumhexaferrite substitution by Mn+2 and Ti+4 ions. In research is not found existence of intermediatephase during formation of the phaseKeywords: recrystalization, high frequency, intermediate phase, ferrites